2023
DOI: 10.3389/fmicb.2023.1145114
|View full text |Cite
|
Sign up to set email alerts
|

A novel Toxoplasma gondii TGGT1_316290 mRNA-LNP vaccine elicits protective immune response against toxoplasmosis in mice

Abstract: Toxoplasma gondii (T. gondii) can infect almost all warm-blooded animals and is a major threat to global public health. Currently, there is no effective drug or vaccine for T. gondii. In this study, bioinformatics analysis on B and T cell epitopes revealed that TGGT1_316290 (TG290) had superior effects compared with the surface antigen 1 (SAG1). TG290 mRNA-LNP was constructed through the Lipid Nanoparticle (LNP) technology and intramuscularly injected into the BALB/c mice, and its immunogenicity and efficacy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Some studies have shown that LNP vectors can effectively deliver mRNA vaccines and stimulate tumor antigen-specific immune responses in tumor mouse models [161][162][163][164] . For example, some mRNA vaccines targeting tumor-specific antigens delivered through LNP carriers can induce high levels of specific antibodies and cellular immune responses, inhibit tumor growth and prolong the survival time of mice [165] .…”
Section: Delivery Mechanism Of Lnps As Mrna Vaccine Carriersmentioning
confidence: 99%
“…Some studies have shown that LNP vectors can effectively deliver mRNA vaccines and stimulate tumor antigen-specific immune responses in tumor mouse models [161][162][163][164] . For example, some mRNA vaccines targeting tumor-specific antigens delivered through LNP carriers can induce high levels of specific antibodies and cellular immune responses, inhibit tumor growth and prolong the survival time of mice [165] .…”
Section: Delivery Mechanism Of Lnps As Mrna Vaccine Carriersmentioning
confidence: 99%
“…The most straightforward measure of a potential vaccine's efficacy is the percentage of vaccinated mice that can still be alive due to the T. gondii challenge. To test the mice's ability to survive, we administered intraperitoneal injections of tachyzoites from the extremely dangerous T. gondii RH strain(32). In our study, within 12 days of the RH tachyzoite test, every mouse in group IV perished.…”
mentioning
confidence: 99%